Differential Germination and Growth Response to Temperature of Three Ambrosia Weed Species—Implications for Future Spread - Yair, Yifat; Goldwasser, Yaakov; Sibony, Moshe; Eizenberg, Hanan; Rubin, Baruch (Frontiers in Agronomy, 2020)
Three main Ambrosia species (Ragweed)grow in Israel of which A. artemisiifolia and A. tenuifolia are of restricted distribution and the invasive A. confertiflora is the most abundant and widely distributed in roadsides, open land, waterways and cultivated fields and orchards. The present research was aimed to study the effect of temperatures regimes on the development and growth of the three main Ambrosia species in Israel, to elucidate the environmental conditions and plant traits that affect their development and infestation patterns. Seed germination studies were conducted in petri dish and pots. Ambrosia spp. plant emergence and development kinetics of different organs were conducted in pots and trays in a net house and at different temperature regimes in a phytotron. A. confertiflora, A. artemisiifolia and A. tenuifolia germinate best in light from the soil surface with no prerequisite of a stratification period. A. confertiflora seed emergence is inhibited at high temperature regimes (28-34ºC), A. artemisiifolia at low temperature regimes (10-16ºC) C, while A. tenuifolia is less affected by the temperature regimes. A. confertiflora plant height increased with increasing temperatures, and at lower temperatures develops a rosette. Root and rhizome biomass was less affected by the different temperatures regimes, A. artemisiifolia overground mass was not affected by temperature regimes while A. tenuifolia overground mass was reduced only at lower temperatures. The factors affecting A. confertiflora fast invasion and establishment are: easy long-distance seed dissemination, prolific seed germination and sprouting of rhizomes, rapid growth, massive viable seed fecundity, and adaptation to changing and adverse environmental conditions.